Origin of OXA-23 Variant OXA-239 from a Recently Emerged Lineage of Acinetobacter baumannii International Clone V - Lucía Graña-Miraglia; Benjamin A. Evans; Luis Esaú López-Jácome; Melissa Hernández-Durán; Claudia Adriana Colín‐Castro; Patricia Volkow-Fernández; Miguel A. Cevallos; Rafael Franco‐Cendejas; Santiago Castillo‐Ramírez (2020)
Over the last few decades, carbapenemase-producing Acinetobacter baumannii has become a major cause of nosocomial infections all over the world. However, the genome identity of lineages of this species in Latin America has not been studied as much as in developed countries. Here, through a population genomics approach considering the whole genomes of 148 isolates (almost 40 from Mexico and Honduras), we describe the recent emergence of the lineage sequence type 758 (ST758), which belongs to the international clone V and has spread out to Canada, Mexico, Honduras, and Colombia. Notably, this lineage was found to coexist with other A. baumannii lineages in hospitals in Mexico and Honduras. Isolates from this lineage show considerable variation in antibiotic resistance profiles, but most of them are resistant to carbapenems. Moreover, we found a variety of acquired oxacillinase (OXA) families within this lineage and tracked the very recent inception, and subsequent horizontal transmission, of the OXA-239 carbapenemase. This work highlights the urgent need to investigate recently emerged lineages of this species in Latin America and elsewhere, as these might harbor novel antibiotic resistance genes.IMPORTANCEA. baumannii is a major cause of nosocomial infections all over the world. Although many isolates from developed countries have been studied in terms of their genome sequence, isolates from Latin America have been much less studied. In this study, using a population genomics approach considering the whole genomes of 148 isolates, we describe the recent emergence of the lineage ST758 endemic to Latin America and the inception of the OXA-239 carbapenemase. Our study highlights the urgent need to investigate recently emerged lineages of this species in Latin America and elsewhere, as these might harbor novel antibiotic resistance genes.